Crosslinked polystyrene dielectric film as well as preparation method and application thereof
By introducing nitrostyrene into polystyrene dielectric films and employing blade coating and photocrosslinking techniques, the problem of performance degradation of polymer film capacitors at high temperatures has been solved, achieving improved high dielectric constant and breakdown strength, making it suitable for high-temperature resistant polymer film capacitors.
Patent Information
- Application Number
- CN202511579620.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-31
- Publication Date
- 2025-12-12
AI Technical Summary
Existing polymer film capacitors exhibit performance degradation at high temperatures. Their low dielectric constant and low breakdown strength result in low discharge energy density, failing to meet the miniaturization and high-temperature resistance requirements of the electronics industry.
By introducing nitrostyrene into polystyrene dielectric films, cross-linked polystyrene dielectric films are prepared using blade coating and photocrosslinking methods, thereby improving the glass transition temperature, dielectric constant, and breakdown strength of the material.
The prepared cross-linked polystyrene dielectric film has a high glass transition temperature and high breakdown strength, making it suitable for high-temperature polymer film capacitors and improving energy density and high-temperature resistance.
Smart Images

Figure CN121108394A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer materials, and more specifically, to a cross-linked polystyrene dielectric film, its preparation method, and its application. Background Technology
[0002] Polymer film capacitors possess characteristics such as ultra-high power density, fast charging and discharging speed, lightweight, safety, low cost, good self-healing properties, and long cycle life, making them widely used in electronic devices and power systems. However, with societal progress and rapid technological development, low energy density polymer film capacitors can no longer meet the miniaturization and lightweight requirements of today's electronics industry. For example, commercially available biaxially oriented polypropylene (BOPP) film capacitors have an energy density of only 1-2 J·cm⁻¹. -3 Furthermore, the development of industries such as underground oil and gas exploration and space shuttles has placed higher demands on the high-temperature resistance of film capacitors. However, BOPP film capacitors operate at temperatures below 85°C. For high-temperature operation, a large and bulky cooling system is required. Therefore, in order for polymer film capacitors to match the development of the electrical age, there is an urgent need to develop high-energy-density, high-temperature-resistant dielectric materials for energy storage capacitors.
[0003] Linear polystyrene dielectric materials possess excellent processability, low cost, low dielectric loss (tanδ), and high charge / discharge efficiency, which are beneficial for the large-scale industrial production of polymer film capacitors. However, their drawbacks lie in their low dielectric constant and low breakdown strength, with values of approximately 2.4–2.7 (1 kHz) and 200 (MV / m), respectively. These low dielectric constant and breakdown strength result in low discharge energy density. Furthermore, linear polystyrene has a low glass transition temperature and poor heat resistance, leading to a significant performance degradation of polymer film capacitors at high temperatures, making it difficult to meet the requirements for next-generation high-temperature resistant polymer dielectric materials.
[0004] Therefore, new technologies need to be developed to improve the dielectric constant, breakdown strength, and glass transition temperature of polystyrene dielectric materials. Summary of the Invention
[0005] The primary objective of this invention is to overcome the technical problems existing in the prior art and to provide a method for preparing cross-linked polystyrene dielectric films.
[0006] A further object of the present invention is to provide a cross-linked polystyrene dielectric film.
[0007] A further object of the present invention is to provide an application of cross-linked polystyrene dielectric film in the preparation of capacitors.
[0008] The above-mentioned objective of the present invention is achieved through the following technical solution: A method for preparing a cross-linked polystyrene dielectric film includes the following steps: S1. Styrene, divinylbenzene, nitrostyrene, thermal initiator and solvent are mixed to obtain a mixed solution, and then a prepolymerization reaction occurs to obtain a prepolymer solution; S2. The prepolymer solution is mixed with a photoinitiator, then coated into a film, and then photocrosslinked to obtain the crosslinked polystyrene dielectric film; In step S1, the mass ratio of styrene to nitrostyrene is 100:(4~26).
[0009] Studies have shown that cross-linked polystyrene has a higher glass transition temperature than linear polystyrene.
[0010] The inventors of this invention have discovered that introducing a certain amount of nitrostyrene containing strong electron-withdrawing and large-volume nitro groups into cross-linked polystyrene can not only further increase the glass transition temperature of the material, but also increase the dielectric constant and breakdown strength of the cross-linked polystyrene dielectric film. However, as the amount of nitrostyrene increases, the breakdown strength of the cross-linked polystyrene dielectric film first gradually increases and then gradually decreases; therefore, the amount of nitrostyrene used should not be too high.
[0011] Since nitrostyrene is introduced into the polymer film as a monomeric raw material, and the thickness of the dielectric film is usually thin (5-30 micrometers), the cross-linked polystyrene dielectric film of the present invention needs to be prepared by blade coating. Blade coating requires the combination of prepolymerization (thermal polymerization) and photocrosslinking. Without prepolymerization, it is difficult to perform the blade coating in step S2; without photocrosslinking, it is impossible to finally produce the cross-linked polystyrene dielectric film.
[0012] In this invention, the mass ratio of styrene to nitrostyrene can specifically be 100:4, 100:5, 100:8, 100:10, 100:12, 100:15, 100:17, 100:18, 100:20, 100:22, 100:25, 100:26, or a range formed by any two of the above values.
[0013] Preferably, the mass ratio of styrene to nitrostyrene is 100:(10~25), more preferably 100:(17~25). Further adjusting the mass ratio of styrene to nitrostyrene can result in higher breakdown strength of the cross-linked polystyrene dielectric film.
[0014] Preferably, the mass ratio of styrene to divinylbenzene is 97~99:1~3.
[0015] Preferably, the divinylbenzene is at least one of o-divinylbenzene, m-divinylbenzene, or p-divinylbenzene.
[0016] Preferably, the nitrostyrene is at least one of p-nitrostyrene and m-nitrostyrene.
[0017] Preferably, the concentration of styrene in the mixed solution is 30-50 wt%.
[0018] Preferably, the thermal initiator is at least one of azobisisobutyronitrile or benzoyl peroxide.
[0019] Preferably, the amount of the thermal initiator is 0.1 to 1 wt% of the mass of styrene.
[0020] Preferably, the solvent is at least one of toluene, tetrahydrofuran, or chloroform.
[0021] Preferably, the temperature of the prepolymerization reaction is 60~90℃; specifically, it can be 60, 70, 80, or 90℃.
[0022] Preferably, the prepolymerization reaction takes 1 to 3 hours.
[0023] Preferably, the prepolymerization reaction is carried out in an inert atmosphere (such as a nitrogen atmosphere).
[0024] Preferably, the photoinitiator is at least one of 2-hydroxy-2-methylphenylacetone and diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide.
[0025] Preferably, the amount of photoinitiator is 0.1 to 1 wt% of the mass of styrene.
[0026] Preferably, the conditions for photocrosslinking are: ultraviolet light irradiation for 20-60 minutes.
[0027] More preferably, the ultraviolet light has a wavelength of λ ≥ 365 nm.
[0028] Preferably, the photocrosslinking is performed in an inert atmosphere (such as a nitrogen atmosphere).
[0029] Preferably, the photocrosslinking process further includes a drying step.
[0030] More preferably, the drying process is as follows: heat treatment at 50~60°C for 8~12 hours, and then heat treatment at 90~120°C for 4~6 hours.
[0031] Preferably, the thickness of the cross-linked polystyrene dielectric film is 5 to 30 micrometers.
[0032] A cross-linked polystyrene dielectric film is prepared by the above-described method.
[0033] The application of the aforementioned cross-linked polystyrene dielectric film in the preparation of capacitors is also within the scope of protection of this invention.
[0034] A capacitor comprising the aforementioned cross-linked polystyrene dielectric film.
[0035] Compared with the prior art, the beneficial effects of the present invention are: The cross-linked polystyrene dielectric film prepared by the method of the present invention not only has a glass transition temperature, but also has a high dielectric constant and breakdown strength, making it very suitable for preparing polymer film capacitors, especially high-temperature resistant polymer film capacitors. Attached Figure Description
[0036] Figure 1 a is a physical image of the cross-linked polystyrene dielectric film of Example 1. Figure 1 b is the DSC curve of the dielectric thin film of Example 1, Comparative Example 1 and Comparative Example 2.
[0037] Figure 2 The graph shows the dielectric constant test results of the dielectric films of Example 1, Comparative Example 1, and Comparative Example 2.
[0038] Figure 3 The graph shows the dielectric loss test results of the dielectric films of Example 1, Comparative Example 1, and Comparative Example 2.
[0039] Figure 4 The Weibull distribution of the breakdown strength of the dielectric films of Example 1, Comparative Example 1, and Comparative Example 2 at room temperature is shown.
[0040] Figure 5 The graph shows the test results of the breakdown strength of the dielectric films of Examples 1-4 and Comparative Examples 1-2 at room temperature.
[0041] Figure 6 This is an energy density diagram of the dielectric thin film of Example 1 and Comparative Example 2 at room temperature.
[0042] Figure 7 The image shows the energy density of the cross-linked polystyrene dielectric film of Example 1 at 100°C. Detailed Implementation
[0043] To more clearly and completely describe the technical solution of the present invention, the present invention will be further described in detail below through specific embodiments. It should be understood that the specific embodiments described herein are only for explaining the present invention and are not intended to limit the present invention. Various changes can be made within the scope of the claims of the present invention.
[0044] Example 1 This embodiment provides a method for preparing a cross-linked polystyrene dielectric film, comprising the following steps: (1) Weigh 4 mg of azobisisobutyronitrile and pour it into a reaction vessel. Then add 2 g of styrene, 0.35 g of p-nitrostyrene, 36 mg of divinylbenzene (p-divinylbenzene) and 2.5 g of toluene in sequence. Stir magnetically for 10 minutes to obtain a mixed solution. After stirring the mixed solution at 70 °C under a nitrogen atmosphere for 2 hours, a prepolymer solution with a certain viscosity is obtained. (2) After adding 4 mg of 2-hydroxy-2-methylphenylacetone photoinitiator to the prepolymer solution, the mixture was stirred and then poured onto a glass plate. A prepolymer solution film of a certain thickness was obtained by using a 150-micron blade coater. The prepolymer solution film was placed in a UVLED curing light source box, nitrogen gas was introduced, and the prepolymer solution film was continuously irradiated for 30 minutes at a distance of 10 cm from the light source under the conditions of 100W power and λ>365nm ultraviolet light irradiation to obtain a cured film. The cured film was placed in a 55℃ oven for 10 hours to remove the remaining solvent, and then heated to 100℃ for annealing for 5 hours. Finally, the film was peeled off from the glass plate to obtain a cross-linked polystyrene dielectric film with a thickness of about 15 microns.
[0045] Example 2 This embodiment provides a method for preparing a cross-linked polystyrene dielectric film, which differs from Example 1 in that: in step (1), the amount of p-nitrostyrene is adjusted to 0.10g.
[0046] Example 3 This embodiment provides a method for preparing a cross-linked polystyrene dielectric film, which differs from Example 1 in that: in step (1), the amount of p-nitrostyrene is adjusted to 0.22g.
[0047] Example 4 This embodiment provides a method for preparing a cross-linked polystyrene dielectric film, which differs from Example 1 in that: in step (1), the amount of p-nitrostyrene is adjusted to 0.50g.
[0048] Comparative Example 1 This embodiment provides a method for preparing a cross-linked polystyrene dielectric film, which differs from Example 1 in that: in step (1), the amount of p-nitrostyrene is adjusted to 0g, that is, p-nitrostyrene is not added.
[0049] Comparative Example 2 This embodiment provides a method for preparing a polystyrene dielectric film, which differs from Example 1 in that: in step (1), the amount of p-nitrostyrene and divinylbenzene is adjusted to 0g, that is, p-nitrostyrene and divinylbenzene are not added.
[0050] Sample characterization and performance testing 1. Glass transition temperature The glass transition temperature of the sample was determined using a differential scanning calorimeter from Waters, USA. Figure 1 a is a physical image of Example 1. Figure 1 b is the DSC curve of the sample. From Figure 1 As can be seen from a, the cross-linked polystyrene dielectric film of Example 1 exhibits good film-forming properties. From... Figure 1 As can be seen from b, the glass transition temperature of the cross-linked polystyrene dielectric film of Example 1 is 124°C, which is significantly higher than that of Comparative Example 1 (112°C) and Comparative Example 2 (104°C). The glass transition temperatures of the cross-linked polystyrene dielectric films of other examples are similar to those of Example 1, indicating that the cross-linked polystyrene dielectric film of the present invention has a high glass transition temperature.
[0051] 2. Dielectric constant and dielectric loss Dielectric constant and dielectric loss are in the range of 10⁻¹⁰. 6 The frequency range was measured using a broadband dielectric spectrometer (Agilent 4294A, USA). Gold was sputtered onto the upper and lower surfaces of the cross-linked polystyrene dielectric film using a magnetron sputtering apparatus. The electrode thickness was 1 mm, and the electrode area was 3.14 square millimeters. Figure 2 These are graphs showing the dielectric constant test results for Example 1, Comparative Example 1, and Comparative Example 2. Figure 3 These are graphs showing the dielectric loss test results for Example 1, Comparative Example 1, and Comparative Example 2. From... Figure 2 It can be seen that the dielectric constant of the cross-linked polystyrene dielectric film of Example 1 is significantly higher than that of Comparative Example 1 and Comparative Example 2, wherein, at 10... 3 At Hz, the dielectric constant of Example 1 is approximately 3.3. From Figure 3 It can be seen that in Example 1, 10 3 and 10 6 The dielectric loss remains low within the specified frequency range, with a value below 0.008. The dielectric constant and dielectric loss test results of the cross-linked polystyrene dielectric films in other embodiments are similar to those in Example 1.
[0052] 3. Breakdown strength The breakdown strength was measured according to GB1408-78, using a progressive voltage increase rate of 1 kV / s until the dielectric film was broken down. The breakdown strength of the dielectric film was calculated using the two-parameter Weibull statistical method, as shown in the following equation: In the formula, P(E) is the cumulative probability of insulation failure, E is the measured breakdown electric field, and E b The characteristic breakdown strength and shape parameters for a thin-film insulation failure probability of 63.2% are given. β The parameter used to assess data dispersion represents the degree of dispersion of the experimental data. The testing instrument was a TF3000 from AixACT GmbH, Germany.
[0053] Figure 4 The Weibull distribution of the breakdown strength of the dielectric films of Example 1, Comparative Example 1, and Comparative Example 2 at room temperature is shown below. Figure 4 It can be seen that the breakdown strength of the cross-linked polystyrene dielectric film in Example 1 is 613 MV / m, which is much higher than that of Comparative Example 1 and Comparative Example 2.
[0054] Figure 5 The graph shows the test results of the breakdown strength of the dielectric films of Examples 1-4 and Comparative Examples 1-2 at room temperature. From... Figure 5 It can be seen that as the content of nitrostyrene monomer increases, the breakdown strength of cross-linked polystyrene copolymers exhibits a change pattern of first increasing and then decreasing.
[0055] 4. Energy density and charge / discharge efficiency The energy density and charge / discharge efficiency of the polymer were obtained by integrating the PE curve, where the diameter of the gold electrode on the polymer surface was 3 mm. Figure 6 The figures show the energy density and charge / discharge efficiency test results of the dielectric thin films in Example 1 and Comparative Example 2 at room temperature, respectively. Figure 6 It can be seen that the dielectric thin film in Comparative Example 2 has an energy density of 2.5 J / cm². 3 The energy density of the cross-linked polystyrene dielectric film in Example 1 is 5.8 J / cm². 3 .
[0056] Figure 7 This is the energy density diagram of the cross-linked polystyrene dielectric film of Example 1 at 100°C. From... Figure 7 It can be seen that the energy density of Example 1 can still be maintained at 2.4 J / cm³ at 100℃. 3 .
[0057] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the implementation of the present invention. Those skilled in the art can make other variations or modifications based on the above description. It is neither necessary nor possible to exhaustively describe all embodiments here. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the claims of the present invention.
Claims
1. A method for preparing a cross-linked polystyrene dielectric film, characterized in that, Includes the following steps: S1. Styrene, divinylbenzene, nitrostyrene, thermal initiator and solvent are mixed to obtain a mixed solution, and then a prepolymerization reaction occurs to obtain a prepolymer solution; S2. The prepolymer solution is mixed with a photoinitiator, then coated into a film, and then photocrosslinked to obtain the crosslinked polystyrene dielectric film; In step S1, the mass ratio of styrene to nitrostyrene is 100:(4~26).
2. The preparation method according to claim 1, characterized in that, The divinylbenzene is at least one of o-divinylbenzene, m-divinylbenzene, or p-divinylbenzene.
3. The preparation method according to claim 1, characterized in that, The mass ratio of styrene to divinylbenzene is 97~99:1~3.
4. The preparation method according to claim 1, characterized in that, The nitrostyrene is at least one of p-nitrostyrene and m-nitrostyrene.
5. The preparation method according to claim 1, characterized in that, The prepolymerization reaction takes 1 to 3 hours.
6. The preparation method according to claim 1, characterized in that, The conditions for photocrosslinking are: irradiation with ultraviolet light for 20-60 minutes.
7. The preparation method according to claim 1, characterized in that, The thickness of the cross-linked polystyrene dielectric film is 5 to 30 micrometers.
8. A cross-linked polystyrene dielectric film, characterized in that, It is prepared by any of the preparation methods described in claims 1 to 7.
9. The application of the cross-linked polystyrene dielectric film of claim 8 in the preparation of capacitors.
10. A capacitor, characterized in that, Includes the cross-linked polystyrene dielectric film of claim 8.